The role of horizontal cooperation to improve service quality in last-mile distribution. (2018) - Serrano-Hernandez, Adrian; Hirsch, Patrick; Faulin, Javier; Fikar, Christian
Horizontal cooperation has revealed itself as a new catalyser for goods distribution optimisation in order to achieve greater efficiency. Moreover, urban distribution is facing a new paradigm as e-commerce is growing rapidly and traffic restrictions in inner cities are becoming more frequent. While the economic benefit derived from the application of horizontal cooperation has been widely analysed by practitioners and in academia, this paper assesses the impact of horizontal cooperation on service quality in a business-to-business relationship. An agent-based simulation model is presented to measure savings in lead times due to various horizontal cooperation agreements under consideration of trust related factors. Additionally, the effect of the store-wholesaler topology is investigated, providing meaningful insights on the potentials of horizontal cooperation. Results of computational experiments show that cooperation enables companies to reduce lead times substantially, which increases service quality and competitiveness.